Small RNAs in skeletal tissue homeostasis and fracture healing - Bourgery, Matthieu (fi=Turun yliopisto|en=University of Turku|, 2023)
Long bone fracture is a common injury which could result from a fall, shock, sports injury or a disease such as osteoporosis. Fracture healing involves multiple partly overlapping steps including inflammation, endochondral ossification, angiogenesis and remodelling. The high burden of bone fractures on public health as well as economy highlights the importance of understanding the healing process and identifying biomarkers for better management of bone health. This thesis study focused on the expression of small non-coding RNAs (sncRNAs) in bone fracture and fracture healing. SncRNAs are important regulators of gene expression, and they also serve as biomarkers for many diseases. MicroRNAs (miRNAs) have well-characterized functions in the regulation of protein-coding mRNAs. Transfer RNA-derived small RNAs (tsRNAs) are a less well-studied class of sncRNAs, but they are also involved in the regulation of gene expression at various levels. In bone and fracture healing callus tissue the role of tsRNAs have not been studied before. The main aim of the study was to determine the effects of bone fracture on the genome-wide expression profiles of miRNAs and tsRNAs in the callus tissue which forms at the fracture site, as well as in circulation during the healing process in mice. For these purposes, basal (callus tissue) and circulating (serum exosome fraction) RNAs were extracted at different time points after tibial shaft fracture, and tsRNAs and miRNAs were analysed by high-throughput sequencing. Also, mRNA and retrotransposon (LTRs) expression profiles were investigated in fracture callus by high-throughput sequencing. The study revealed differential expression of 54 miRNAs, 7 tsRNA, and 15 LTRs in callus tissue in comparison to intact bone while in circulation 8 miRNAs and 3 tsRNAs were differentially expressed after fracture. Literature searches were performed to identify the target genes for those 54 differentially expressed miRNAs. A significant negative correlation was observed between the expression of 164 miRNA-target mRNA pairs in the callus, suggesting a potential role of these miRNAs as fine-tuners of fracture healing by regulation of the expression of their target mRNAs. These results indicate a role for tsRNAs and miRNAs as regulators of fracture healing in vivo and possibly have potential as systemic biomarkers